Potential of Upland Rice Promising Lines in Acid Dry Land at Two Different Seasons - Eries Dyah Mustikarini; Gigih Ibnu Prayoga; Ratna Santi; Yesi Yesi; Nur Putri Eka Sari (AGRIVITA, Journal of Agricultural Science, 2023)
Superior upland rice varieties can be obtained through the plant breeding process. Upland rice lines that are carried out from crossing have different potentials.Â The research aims to determine upland rice promising lines with high yields in acid-dry land. The study is conducted on Ultisol soil. The first season is in 2019 for F6 lines, and the second is in 2021 for F7 lines. The experimental methods use factorial Randomized Block Design (RBD). The treatment at the preliminary yield test use 5 lines 4 varieties, and 1 landrace. The advanced yield test uses 5 F7 lines (selected from F6 lines) and 5 types. Analysis data use ANOVA and LSI test. The result shows that lines GH8 and GH10 have the highest yields on acid-dry soils during two planting seasons. The GH10 line has a 7.20-9.53 kg/plot yield, and the GH8 line has a 5.22-6.26 kg/plot. The highest yield potential was the GH10 line of 3.69-4.77 t/ha, more increased than Balok, Banyuasin, Danau Gaung, Inpago 8, and PBM-UBB1 varieties. GH10 and GH8 lines are recommended as candidates for new superior varieties of upland rice that are adaptive to acid-dry soils.